2009
DOI: 10.1098/rspb.2009.0457
|View full text |Cite
|
Sign up to set email alerts
|

Great tits growing old: selective disappearance and the partitioning of senescence to stages within the breeding cycle

Abstract: Deterioration of reproductive traits with age is observed in an increasing number of species. Although such deterioration is often attributed to reproductive senescence, a within-individual decline in reproductive success with age, few studies on wild animals have focused on direct fitness measures while accounting for selective disappearance and terminal effects, and to our knowledge none have determined how senescence effects arise from underlying reproductive traits. We show for female great tits that such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
281
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(304 citation statements)
references
References 56 publications
20
281
3
Order By: Relevance
“…During such endeavours it remains important to pay attention to constraints other than work level, especially time limitations, that may prevent animals from eating for long enough to keep up with the high energy expenditure (Tinbergen and Verhulst, 2000;Kvist and Lindström, 2000). When interpretable aspects of the ecological context can be linked to maximal performance, or rather to the relationships between experimentally manipulated work levels and both reproduction and survival (Fig.4) [see Bouwhuis et al for a possible field setting (Bouwhuis et al, 2009)], we may achieve deeper levels of understanding of the selection factors driving the height of metabolic ceilings.…”
Section: Towards An Ecology Of Physiological Constraintmentioning
confidence: 99%
“…During such endeavours it remains important to pay attention to constraints other than work level, especially time limitations, that may prevent animals from eating for long enough to keep up with the high energy expenditure (Tinbergen and Verhulst, 2000;Kvist and Lindström, 2000). When interpretable aspects of the ecological context can be linked to maximal performance, or rather to the relationships between experimentally manipulated work levels and both reproduction and survival (Fig.4) [see Bouwhuis et al for a possible field setting (Bouwhuis et al, 2009)], we may achieve deeper levels of understanding of the selection factors driving the height of metabolic ceilings.…”
Section: Towards An Ecology Of Physiological Constraintmentioning
confidence: 99%
“…To assess how declining individual performance versus earlier mortality of low-quality individuals shape demographic processes and hence selection pressures, it is necessary to simultaneously estimate functional declines and selective disappearance in a population. So far, few studies have taken this approach [10,12,13], and thus the relative importance of these processes within populations and across taxa is largely unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in mortality probably results from functional senescence (FS, within-individual deterioration of physical or physiological functioning with advancing age), which, along with terminal disease or investment in reproduction at the expense of maintenance [5][6][7][8], can expose individuals to extrinsic hazards in a condition-dependent manner. Therefore, only high-quality individuals may survive to an age where FS takes effect, making ageing difficult to observe in cross-sectional studies of natural populations [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This is because as individuals senesce they undergo a decline in residual reproductive value (Fisher 1930) which reduces their reproductive success (Bouwhuis et al 2009;Reed et al 2008). Older males, with reduced ejaculate competitive ability (Jones & Elgar 2004;Dean et al 2010), may therefore increase their overall aggressive interactions towards competitors to prevent sperm competition and protect their paternity.…”
Section: Introductionmentioning
confidence: 99%
“…While it is well established that age can affect direct fitness (Reed et al 2008;Bouwhuis et al 2009), researchers have also suggested implications for inclusive fitness (Libertini 1988;Lee 2003;Bourke 2007;Ronce et al 2010). …”
Section: Introductionmentioning
confidence: 99%